Burden of Prostate Cancer in China, 1990–2019: Findings From the 2019 Global Burden of Disease Study - Wang, Fuquan; Wang, Chenchen; Xia, Haifa; Lin, Yun; Zhang, Dingyu; Yin, Peng; Yao, Shanglong (Frontiers in Endocrinology, 2022)
Prostate cancer (PC) is a malignant tumor derived from prostate epithelial cells and is one of the most commonly diagnosed cancers in men. In recent years, the global incidence and the annual deaths number of PC showed a continuous increase， which has caused a huge disease burden on human health. In terms of the global average, the incidence and mortality of PC in China are relatively low. However, the age-standardized incidence rate of PC was 17.3/100,000 in 2019 in China, with a 95.2% rise compared to 1990, while the global growth rate of incidence rate over the same period is 13.2%. This showed that the development trend of PC in China is not optimistic. There are few precise studies on the epidemiology of PC in China. After the general analysis strategy used in the Global Burden of Diseases, Injuries and Risk Factors Study (GBD) 2019, we elaborated on the incidence, mortality, and disability-adjusted life-years (DALYs) and the corresponding age-standardized rate of the Chinese PC population from 1990 to 2019 according to different ages and provinces. We used joinpoint regression analysis to estimate the incidence and mortality trends. Our analysis shows that elderly people over 80 are still the main focus of incidence and death. The epidemiology and disease burden of PC of different provinces in China show obvious regional differences, and some certain provinces such as HongKong, Macao, and Zhejiang should be paid more attention. More targeted and effective strategies should be developed to reduce the burden of PC in China.